Neuropsychiatry: psychoses that should not always be treated with antipsychotics - Yury P. Sivolap; Anna A. Portnova (LLC "MEDIAFORMAT", 2024)
Disorders manifested by both neurological and mental disorders belong to the neuropsychiatric diseases. This category includes Alzheimer's disease, Parkinson's disease, Wernicke-Korsakoff syndrome, delirium tremens, catatonia and anti-NMDA receptor encephalitis. The etiology of psychotic disorders in neuropsychiatric diseases probably differs from that in schizophrenia and other psychoses, which causes both inefficiency and adverse events when using antipsychotics in neuropsychiatry. In the absence of a therapeutic alternative, antipsychotics can be prescribed with caution for neurodegenerative disorders, whereas catatonia is a relative, and anti-NMDA receptor encephalitis is an absolute contraindication to their use.